The efficacy of intravaginal electrical stimulation (IVES) in treating female with urinary incontinence symptom from meta-analysis of nine randomized controlled trials - Yao, Huibao; Zhang, Xiaofei; Sun, Fengze; Tang, Gonglin; Wu, Jitao; Zhou, Zhongbao (Frontiers in Neurology, 2022)
We conducted a meta-analysis to evaluate the efficacy of intravaginal electrical stimulation (IVES) in the treatment of female urinary incontinence (UI). From January 2006 to December 2021, we finally selected 9 randomized controlled trials (RCTs) including 657 participants from PubMed, EMBASE, and Cochrane databases to evaluate the efficacy of IVES in the treatment of female UI. All the data were analyzed by Review Manager Version 5.4. Compared with control group, there were significant improvements in urine pad test (P=0.01), urinary incontinence frequency (P=0.04), some indicators in the incontinence quality of life questionnaire and King’s health questionnaires, and subjective feeling of cure (P=0.009) in the IVES group. However, in other indicators reflecting UI, there was no significant difference between IVES group and control group. In summary, IVES can partially improve the symptoms of female patients with UI compared with the control group.